ANALYZING PEER RELATIONS DURING ADOLESCENCE: A COMPREHENSIVE STUDY - 1. T Arun Christopher , 2. KVSN Murty, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This study investigates the multifaceted attributes of peer relations during adolescence, a critical period marked by social and emotional development. Grounded in the survey research design, the study aimed to assess the dynamics of peer interactions among higher secondary students in Kanchipuram district. A stratified random sampling technique was employed to select a representative sample of 1,300 students, ensuring diversity across various demographic segments (Creswell, 2014). The study utilized Walter W. Hudson’s Index of Peer Relations Scale, a validated instrument renowned for its reliability in assessing peer-related behaviors and attitudes (Hudson, 1982). Exploratory Factor Analysis (EFA) was conducted to identify latent variables underlying peer relations (Fabrigar & Wegener, 2011). The analysis revealed five core constructs: peer treatment, peer attitude, peer connectivity, peer issues, and peer isolation. These constructs encapsulate the diverse dimensions of peer interactions, ranging from positive engagement to social exclusion. Subsequently, regression analysis was employed to develop a predictive model of peer relations (Field, 2013). The model demonstrated significant correlations between peer attitude and connectivity, highlighting the role of supportive and positive peer environments in fostering adolescent well-being (Wentzel, 2017). Conversely, peer issues and isolation emerged as critical factors contributing to social anxiety and academic disengagement (Rubin et al., 2009). The findings underscore the importance of fostering inclusive and supportive peer environments to enhance adolescent social development. Future research could explore longitudinal data to further validate the model and examine the long-term impact of peer relations on academic achievement and emotional well-being.